Individual differences in associative/semantic priming: Spreading of activation in semantic memory and epistemically unwarranted beliefs. - Daniel Huete-Pérez; Robert Davies; Javier Rodríguez-Ferreiro; Pilar Ferré (PLoS ONE)
Starting from the enhanced spreading of activation through semantic memory (one of the explanatory mechanisms attempting to explain some manifestations observed in schizophrenia) and the psychosis continuum (a dimensional approach to psychotic disorders, where 'normality' and 'psychopathology' are not qualitatively different in nature but placed on varying levels of the same continuum), the main aim of the present research was to explore whether there are individual differences in associative/semantic priming in people with different levels of epistemically unwarranted beliefs (EUB). Participants varying in paranormal, pseudoscientific and conspiracy endorsement completed a primed lexical decision task containing related prime-target words (e.g., bulb-light) and unrelated prime-target words (e.g., sock-light). Bayesian linear mixed-effects models over response times (RTs) revealed a main direct priming effect (faster RTs in related pairs than in unrelated ones), a main facilitatory effect for some EUB scores (i.e., the higher the value for EUB score, the faster RTs), and an interactive effect between the experimental manipulation and some EUB scores (the higher the EUB score, the smaller the direct priming effect). These results are consistent with predictions made from the enhanced spreading of activation explanatory mechanism, but other alternative accounts are also discussed.